The Influence of Occupational Sensory on Fine Motor Skills in Early Childhood - Lestari, Wiji Sri; Kuswanto, Cahniyo Wijaya (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
This research aims to determine the impact of occupational sensory play on the fine motor skills of early childhood. The method used is a quantitative approach involving 30 children aged 5 to 6 years from RA Al-Hikmah Kedaton in Bandar Lampung. The sampling technique used was a purposive sampling method. Data were collected through various methods, including questionnaires to assess occupational sensory abilities and fine motor skills, observations to record children's behaviour during the intervention, and documentation to supplement the information. Data analysis was conducted using descriptive statistics to provide an overview, t-tests to assess significance, and R² tests to determine the proportion of explained variance. The results indicate that certain components of sensory play particularly variable X7 have a significant impact on children's fine motor skills. However, overall, the application of occupational sensory play does not show statistical significance. The R² value indicates that the independent factors examined explain most of the variance in children's fine motor skills. These findings are useful for determining the effectiveness of sensory play therapy in early childhood development and emphasise the need for further research on specific activities that influence children's fine motor skills. This research adds value by identifying components of sensory play that have the potential to enhance fine motor skills, thus serving as a reference for future occupational therapy practices.